Open innovation ecosystems: toward low-cost wind energy startups. Issue 5 (11th March 2020) - Alam, Muhammad Aftab; Ansari, Kashif Mateen
Abstract : Purpose: The purpose of this paper is to demonstrate how an open innovation strategy of public management in the energy sector enables the creation of innovation ecosystems and how it reduces the cost of wind energy projects in energy-poor countries. Design/methodology/approach: This research study reflects on seven wind energy startups (WESs) in Pakistan using quantitative and qualitative data following a sequential mixed-methods approach. First, it draws from growing literature on innovation and renewable energy management to conceptualize an open innovation ecosystem model around WESs. It then tests this model using cost analyses of wind projects and identifies possible cost-saving strategies. Finally, follow-up interviews with managers in investigated projects cross check study findings and validate the model. Findings: Three noteworthy findings can help policymakers in developing countries to effectively meet the future energy challenges and get benefit from international funding opportunities: by protecting lenders on approved terms rather than offering sovereign guarantee to operating firms; by letting the government take control of the initial development phase; and by giving off-take guarantees to the manufacturers. Practical implications: It offers policy recommendations to energy sector managers about guarantees, financing, regulators, governmental control, tariffs and transfer of technology that can significantly curtail outlays. Originality/value: Results suggest that adopting an open innovation ecosystem model can potentially save around 6 per cent (4-7m) in the overall cost of a 50 MW wind energy project.